KAJIAN ETNOZOOLOGI UNTUK PENGOBATAN SUKU DAYAKSEBARUK DI DESA SETUNGGUL KECAMATAN SILAT HILIR KABUPATEN KAPUAS HULU - Krisyanto, Ruly Dandy; Ardian, Hafiz; Anwari, M Sofwan (Universitas Tanjungpura, 2019)
Humans couldn’t be separated from the use of various biological resources. Resources for the utilization of fauna used for food, medicine, traditional ceremonies, mistycal and art. One of the indigenous ethnic found in the West Kalimantan province is the Dayak Sebaruk in Setunggul Village. The Dayak Sebaruk people also has diversity in ultilization for foods, medicine, traditional ceremonies, mistycal and art. This research objective is expected to provide information about the local knowledge of Etnozoology such as to obtain the animal species and the animal ultilization by Dayak Sebaruk Community in Setunggul Village, Silat Hilir District, Kapuas Hulu Regency. The method used a survey, the selection of respondent were choosing by snowball sampling technique and data collecting used questionnaire. This research were obtained 15 male respondent. The result of the research reaveling there are 10 species of animal ultilization for medecine. Body parts that are ultilized for medicine are the whole body, bile, bounce, bones, fat, reed, fins,blood, honey and thorns.How to processing with dried, poured boling water, burned, fried fat, take blood and honey. How to used by drink, spread and stabbed with chicken feathers in the back of the body with lamp.Keywords :Ethnozoolical, Medicine, Dayak Sebaruk, Setunggul Village